Preventing Age Related Fertility Loss (Springer International Publishing, 2018)
This unique book provides expert advice on all the different aspects related to fertility preservation for age related infertility. Although, there is a lot of information about fertility preservation for cancer treatment available, there is little information for young women. While men have been able to cryopreserve sperm since the 1950s, women have only recently gained the opportunity to preserve their gametes through the egg vitrification technique. Therefore, many women confronted with a risk of imminent fertility loss, such as chemotherapy, are now freezing their oocytes instead of embryos. Successful oocyte cryopreservation offers them a reproductive autonomy independent of men.